Relationship between Breastfeeding and Severe Early Childhood Caries - P. Bořilová Linhartová; M. Kukletová; L. Izakovičová Hollá (Czech Dental Chamber, 2018)
Introduction and aim: Results of research and opinions on breastfeeding in relation to the development of early childhood caries (ECC) are often controversial. The aim of this study was to analyze the state of teeth of Czech children with primary dentition depending on the time for which they were breastfed, eating habits and the level of their oral hygiene. Methods: This retrospective study comprised 424 children of Czech nationality from the Olomouc and South Moravian regions, whose parents signed informed consent and participated in the questionnaire survey. The questionnaire contained four sets of questions focused on anamnestic data, duration of breastfeeding, intake of sweetened soft drinks and child's oral hygiene. A prerequisite for inclusion in the study was eruption of at least 16 primary and the absence of a permanent tooth in the generally healthy child (also without overweight or obesity). In children, we recorded dmft index (decay/missed/filled teeth) and gingival condition. Data evaluation was performed using statistical software Statistica v. 13.2. Results: Of the total set of 424 children (230 boys and 194 girls; mean age ± standard deviation: 4.0 ± 1.1 years), 149 were children with intact primary dentition (dmft = 0) and 275 children with severe ECC (sECC, dmft ≥ 6). In children with sECC, the parents reported in the questionnaire that they served the children more often sweetened beverages and started cleaning their teeth at the age of one year versus the parents of children with the intact dentition (89.9% vs. 65.0%, p < 0.0001, and 80.5% vs. 40.7%, p < 0.0001). 90.7% of children were breastfed, 52.2% of them longer than six months and 5.6% (23 children) even longer than 24 months. After stratification of children to three groups according to the duration of breastfeeding (Group I: ≤ 6, Group II: 6 < and ≤ 24, Group III: > 24 months, no statistically significant difference in the level of oral hygiene in the children in the individual groups was recorded in contrast to the parameter of serving sweetened beverages (p < 0.05). Parents of 77.3% children in Group III reported they started cleaning their children's teeth only after one year of age; 86.4% of them served sweetened liquids to their children, this summarily corresponds to the most risk behavior. Further, we found that the children in Group II had statistically significantly lower risk of the sECC development than the children in Group I (p < 0.001) or children in Group III (p < 0.01). Behavior of parents was analyzed using a correlation matrix and a behavioral pattern related to oral health of their children was found. Conclusion: Many factors play a role in the etiopathogenesis of ECC; our results suggest that breastfeeding of children in the duration of 6 to 24 months appears to be a protective factor for this infectious disease. On the contrary, serving sweetened drinks and late start of oral hygiene was associated with sECC. Breastfeeding longer than two years is connected with risk behavior of mothers/caregivers which can result in the development of sECC.